Pentingnya Protokol Kesehatan dalam Pengimplementasian Nilai-Nilai Agama Islam - Lanina Budi Karsa; Isna Nurhayati; Sinta Susanti; Sofi Fadillah Hendiyani; Ani Nur Aeni (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Community service activities carried out by a team from the Indonesian Education University majoring in PGSD which were held on November 2, 2021 online face-to-face via Zoom have made a very meaningful contribution to the community, especially in the Sumedang Regency area, and received a very good response and enthusiasm. tall. The implementation of community service activities through the outreach program on the Importance of Health Protocols in the Implementation of Islamic Religious Values is intended to help outreach to the community, especially for parents, teachers, and students as prospective educators about the importance of health protocols. This activity aims that we always maintain hand hygiene to support the government's efforts in suppressing cases of the spread of the Corona Virus and raise awareness in the implementation of maintaining cleanliness is part of faith. As we all know, the COVID-19 virus is currently sweeping the world, including Indonesia being one of the countries affected by the pandemic. The government's efforts to suppress the spread of the corona virus continue to be carried out. One of them is in the health sector in preventing the spread of the Corona Virus, namely by carrying out the 3M movement (Washing Hands, Keeping Your Distance and Staying Away from Crowds). Hand washing is a form of maintaining cleanliness. Islam is a religion that pays attention to cleanliness.